Clinical profile and hospital outcomes of children with Down syndrome diagnosed with congenital heart disease in a developing country: A retrospective study - Zawadi Edward Kalezi; Jimmy France Mchalange; Naizihijwa Gadi Majani; Alphonce Nsabi Simbila; Vivienne Aiyana Mlawi; Deogratias Arnold Nkya; Peter Richard Kisenge (PLoS ONE, 2026)
Background The World health organization (WHO) identifies Down syndrome (DS) as one among common congenital disorders, along with congenital heart defects. Approximately fifty percent of children diagnosed with DS are affected by congenital heart defects which significantly impact their survival. Nevertheless, in low and middle income countries, there is limited published data on congenital heart defects in children with DS and their treatment outcomes. Therefore, this study aimed to document the clinical characteristics and hospital outcomes of children with DS who were diagnosed with heart defects. The goal is to assist healthcare providers and policymakers in improving care for these children. Methods This was a retrospective descriptive study of children with DS diagnosed with heart disease admitted at the Jakaya Kikwete Cardiac Institute (JKCI) from December 2022 through December 2024. Socio-demographics, clinical characteristics, and survival data were extracted from medical records. Frequencies and proportions were calculated for categorical variables. The description of mean with standard deviation (SD) and median with and interquartile range (IQR) were calculated for continuous data. For the missing data, the case deletion approach was used. Results In two years, out of 1,356 admitted children, data from 104 children with Down syndrome were analysed. Most of them, 93.2%, were aged below 5 years, with a slight predominance of male children, of almost 58%. Fifty percent (58/104) of study participants resided in the coastal region of Tanzania, followed by the northern zone (19.2%, 20/104). The most frequent cardiac diagnoses were AVSD, 46.2% and VSD, 14.4% with a median age at diagnosis of 5 months (IQR, 3.3–10). The median age of the mothers was 38 years (IQR, 38–42) while the mean age of the fathers was 36.9 years (SD, ± 7.1). At discharge, nearly a quarter, 19.2% of children had prolonged hospital stays of more than 2 weeks, and 7.7% (8/104) of enrolled children died. Nevertheless, 4.8% of children with Down syndrome underwent open cardiac surgery during the study period. Conclusion Advanced maternal age, paternal age and AVSD were frequently observed in this study, nevertheless; a significant number of the enrolled children were first diagnosed beyond 5 months of age. Hence, the study recommends early screening echocardiography among children with Down syndrome and more studies with a large sample size to evaluate long-term outcomes in this population.